Peran Hukum dalam Pembangunan Ekonomi Nasional dan Industri Halal di Indonesia - Saniah, Iah; Sholihah, Nurlailiyah Aidatus (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2024)
This study aims to explain the role of law in national economic development and halal industry in Indonesia. The writing method uses qualitative, primary and secondary data sources obtained from literature studies related to the role of law in national economic development and the halal industry, types of data in the form of qualitative, data collection techniques in the form of previous research, data analysis techniques in the form of descriptive. Based on research conducted, it shows that the halal industry in Indonesia has laws and regulations in building the national economy, and the halal industry. According to the Ministry of Finance of the Republic of Indonesia 2019, the halal industry plays an important role in building economic growth, one of which is the halal industry has donated, namely an investment of USD 1 billion, and has opened 127 thousand jobs every year. Based on the results of this study, it is stated that the role of law in national economic development and the halal industry in Indonesia is an appropriate regulation, such as designing halal industry norms and rules through halal certification, and can build growth and development of the national economy